Hg (II) and Cd (II) Heavy Metal Ions Detection Based On Fluorescence Using Zn (II) Metal Ion Complex with Pyrazoline Derivatives Ligand - Yulian Syahputri; Sutanto Sutanto; Riza Shabrina Zamzani (Helium: Journal of Science and Applied Chemistry, 2022)
Pyrazoline derivatives can be used as ligands because they have photophysical properties and can chelate metal ions which cause  very strong absorption, emission and have a fluorescence properties. Therefore, in recent years, pyrazoline ligands and their derivatives have been widely used for chemosensors. This research aims to detect fluorescence-based heavy metal ions Hg2+ and Cd2+ using a metal ion complex compound Zn2+ with pyrazoline derivative ligand. The research was started by synthesizing pyrazoline-derived ligands, then synthesizing complex compounds. Complex compounds were characterized using Fourier Transform Infra Red (FTIR), UV-Vis Spectrophotometer, and Spectrofluorometer. Then, a fluorescence study was carried out to determine the type of fluorosensor for complex compounds with the addition of heavy metal ions Cd2+ and Hg2+. The last stage is UV-Vis spectroscopy study on the addition of heavy metal ions Hg2+ and Cd2+.  Pyrazoline derivative ligand obtained as para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazole-5-yl)benzene is a yellow solid. The metal ion complex compound Zn2+ with pyrazolin derivative ligand is a brown colored compound, has a yield of 45 % and a melting point is 245 oC. The FTIR spectrum showed the presence of functional groups such as amine, C-H aromatic, C=N, C=C aromatic, C-N, Zn-N and Zn-Cl. Analysis with UV-Vis spectrophotometer showed that there was a shift in the maximum wavelength from the ligand to the Zn(II)-ligand complex, namely 240 nm to 246 nm and 363 nm with molar absorptivity values (log ) of 4.56 and 4.28, respectively. For fluorescence analysis, two absorbance peaks were obtained, namely at a wavelength of 370 nm with an intensity of 3644 a.u and 478 m at 8216 a.u. The results of fluorescence chemosensor studies on the addition of heavy metal ions Hg2+ and Cd2+ showed that the metal ion complex compound Zn2+ with pyrazoline-derived ligands can detect heavy metal ions Hg2+ and Cd2+ with a turn-on type.